The Influence of Hellenistic and Flourishing of Islamic Philosophy in the Modern Age - Muhammad Ikhsan Attaftazani (Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
This study aims to look at how Islam—besides the Orthodox—can accept Greek traditions that are not derived from Islamic sources. Since the Prophet Muhammad's time, Muslims tend to reject sources that come from Jews and Christians who are considered to have reduced the facts. Noteworthy, Civilization's progress in the Islamic world is inseparable from Greek traditions such as philosophy, medicine, and others that originated from Hellenism. The entry of this tradition gave enthusiasm to Muslim scholars to translate Greek works into Arabic. The Greek tradition, especially philosophy, gave distinguished names such as Ibn Sina and al-Farabi. However, after entering the early 15th Century, the study of philosophy stagnated until the 19th century. The Islamic world's scientific condition is far below the progress of the Western nations, both in technology, economics, and education. Modern Century Muslim thinkers realized that they had fallen behind the West and had to pursue it by reforming Islam. Islamic reformers emerged from various Islamic worlds such as Egypt, India, Turkey, and Southeast Asia countries.